Empowering local research ethics review of antibacterial mass administration research - Nelson K. Sewankambo; Paul Kutyabami (BMC, 2022)
Abstract Background Recent studies using mass drug administration (MDA) of antibiotics to entire communities have focused global attention on the unique ethical challenges of MDA of antibiotics in research and public health interventions. However, there is no specific guidance for Research Ethics Committees (RECs) or Institutional Review Boards (IRBs) to review such trials. We surveyed the literature to identify the unique ethical challenges and to strengthen the competencies of RECs or IRBs in low- and middle-income countries (LMICs) in their ethical reviews of these trials. Methods We employed a desk review. We searched PubMed, Web of Science, and Google Scholar, combining terms for "mass drug administration" with terms for "research ethics committees," "institutional review boards," and "ethics." We reviewed citations of search results to retrieve additional articles. Only articles published and indexed in the above databases up to 6 January 2022 in English were included. Abstracts (without full articles), books and articles that had exclusive veterinary and environmental focus were excluded. We synthesized the literature to identify particularly challenging ethical issues relevant to antibacterial MDA trials in LMICs. Results The most challenging ethical issues can be categorised into four broad domains: determining the social value of MDA, assessing risks and benefits, engaging all stakeholders meaningfully, and study design-related ethical challenges. These four domains interact and impact each other. Together, they reveal the need for RECs/IRBs to review MDA studies through a broader lens than that of clinical trials per se. From our findings, we propose a framework to guide the RECs and IRBs in LMICs to perform the initial and continuing review of antibiotic MDA trials. We also recommend strengthening the competencies of LMIC RECs or IRBs through ongoing training and collaboration with RECs or IRBs from high-income countries. Conclusions REC/IRB review of research using MDA of antibiotics plays a critical role in assuring the ethical conduct of MDA studies. Local RECs/IRBs should be empowered to review MDA studies comprehensively and competently in order to advance scientific knowledge about MDA and promote improved global health.